Advances in the Progression and Prognosis Biomarkers of Chronic Kidney Disease - Yan, Zhonghong; Wang, Guanran; Shi, Xingyang (Frontiers in Pharmacology, 2021)
Chronic kidney disease (CKD) is one of the increasingly serious public health concerns worldwide, as well as the global burden of CKD is increasingly carried by the high morbidity and mortality. At present, three key problems are consisted in clinical treatment and management of CKD. Firstly, the current diagnostic indicators, such as proteinuria and serum creatinine, are greatly interfered by the physiological conditions of patients, and the changes of indicator level are not synchronized with renal damage. Secondly, establish diagnosis still depends on biopsy in someone presenting with suspected CKD, which is not only not suitable for contraindication patients, but also traumatic, and is not sensitive to early progression. Finally, the prognosis of CKD is affected by many factors, it is urgent to develop effective biomarkers to predict the CKD prognosis and improve the prognosis through early intervention. Accurately progression monitoring and prognosis improvement of CKD are extremely significant for improving the clinical treatment and management of CKD and reducing the social burden. Therefore, biomarkers reported in recent years, which could play important roles in accurate progression monitoring and prognosis improvement of CKD, were concluded and highlighted in this review article that aiming to provide a reference both for the construction of CKD precision therapy system and the pharmaceutical research and development.